Integrasi Pendidikan Islam dan Pendidikan Vokasi: Kajian Pustaka tentang Pemantapan Keahlian dan Nilai Spiritual - Siregar, Zulfikar Ali Buto; Taufiq, Taufiq; Jumadi, Jumadi (Ahdāf: Jurnal Pendidikan Agama Islam, 2024)
This research aims to analyse the integration of Islamic education and vocational education in the context of the era of globalization and the Industrial Revolution 4.0. The research focuses on exploring the urgency, curriculum approach, challenges, and impact of integration on graduates, as well as providing recommendations for holistic and sustainable education policy development. This research uses a library research method with a qualitative approach. Data were collected from various literature sources, such as relevant journals, books, and scientific articles, and then analysed thematically to identify patterns, challenges, and opportunities in the integration of Islamic and vocational education. Research results include: 1) Urgency of Integration: The integration of Islamic and vocational education is becoming increasingly relevant in the era of the industrial revolution 4.0, where the world of work requires human resources who are not only technically skilled but also have strong work ethics and morality. 2) Curriculum Approach: An integrated curriculum that combines technical skills with Islamic values, such as Islamic business ethics and sharia entrepreneurship, is the key to successful integration. 3) Challenges: This integration faces challenges such as differences in curriculum orientation, limited resources, community perceptions, and unsupportive education policies. 4) Impact on Graduates: Integration produces graduates who are balanced between technical competence and spiritual values, have global competitiveness, and contribute positively to society through work ethics and entrepreneurship based on Islam. The findings of this study have important implications for educational policy development, especially in designing an integrated curriculum, providing adequate facilities, and training competent teaching staff. In addition, intensive socialization is needed to change people's perceptions and show concrete evidence of the success of integration.